Tuning friction and slip at solid-nanoparticle suspension interfaces by electric fields - Acharya, B. (Sci Rep, 2019)
We report an experimental Quartz Crystal Microbalance (QCM) study of tuning interfacial friction and slip lengths for aqueous suspensions of TiO(2) and Al(2)O(3) nanoparticles on planar platinum surfaces by external electric fields. Data were analyzed within theoretical frameworks that incorporate slippage at the QCM surface electrode or alternatively at the surface of adsorbed particles, yielding values for the slip lengths between 0 and 30 nm. Measurements were performed for negatively charged TiO(2) and positively charged Al(2)O(3) nanoparticles in both the absence and presence of external electric fields. Without the field the slip lengths inferred for the TiO(2) suspensions were higher than those for the Al(2)O(3) suspensions, a result that was consistent with contact angle measurements also performed on the samples. Attraction and retraction of particles perpendicular to the surface by means of an externally applied field resulted in increased and decreased interfacial friction levels and slip lengths. The variation was observed to be non-monotonic, with a profile attributed to the physical properties of interstitial water layers present between the nanoparticles and the platinum substrate.